Anticonvulsant studies on a traditional antiepileptic mixture used by the Hausa people of north-western Nigeria - U.H. Danmalam; A. Agunu; E.M. Abdurahman; N. Ilyas; M.G. Magaji; A.H. Yaro (Iranian Society of Pharmacognosy, 2017)
Background and objectives: The use of herbal drugs in the treatment of many neurological disorders is gaining popularity in developing countries due to their fewer unwanted side effects, affordability and cultural acceptability. A mixture of three plants roots Calotropis procera (Asclepediaceae), Combretum micranthum (Combretaceae) and Ficus abutilifolia (Moraceae) has been reported in Hausa traditional treatment of epilepsy. We have reported the evaluation of the acute toxicity and anticonvulsant activity of the ethanol extract of this mixture. Methods: The intra-peritoneal medial lethal dose (LD50) of the aqueous ethanol extract of the mixture as well as its anticonvulsive activity against pentylenetetrazole (PTZ), 4-amino pyridine (4-AMP) and maximum electric shock (MES) were evaluated. Results: The mixture at the doses of 25 to 100 mg/kg could not afford a significant protection to mice against PTZ and 4-AMP; however, it significantly delayed the mean onset and reduced the mean recovery time of the animals at the tested doses in 4-AMP test (p